Review of case definitions for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) - Eun-Jin Lim; Chang-Gue Son (Journal of Translational Medicine, 2020)
Abstract Background Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a debilitating disease with unknown causes. From the perspectives on the etiology and pathophysiology, ME/CFS has been labeled differently, which influenced changes in case definitions and terminologies. This review sought to feature aspects of the history, developments, and differential symptoms in the case definitions. Methods A search was conducted through PubMed published to February 2020 using the following search keywords: case definition AND chronic fatigue syndrome [MeSH Terms]. All reference lists of the included studies were checked. Of the included studies, the number of citations and the visibility in the literatures of the definitions were considered for comparisons of the criteria. Results Since the first 'ME' case definition was developed in 1986, 25 case definitions/diagnostic criteria were created based on three conceptual factors (etiology, pathophysiology, and exclusionary disorders). These factors can be categorized into four categories (ME, ME/CFS, CFS, and SEID) and broadly characterized according to primary disorder (ME-viral, CFS-unknown, ME/CFS-inflammatory, SEID-multisystemic), compulsory symptoms (ME and ME/CFS-neuroinflammatory, CFS and SEID-fatigue and/or malaise), and required conditions (ME-infective agent, ME/CFS, CFS, SEID-symptoms associated with fatigue, e.g., duration of illness). ME and ME/CFS widely cover all symptom categories, while CFS mainly covers neurologic and neurocognitive symptoms. Fatigue, cognitive impairment, PEM, sleep disorder, and orthostatic intolerance were the overlapping symptoms of the 4 categories, which were included as SEID criteria. Conclusions This study comprehensively described the journey of the development of case definitions and compared the symptom criteria. This review provides broader insights and explanations to understand the complexity of ME/CFS for clinicians and researchers.